Lebrikizumab: a novel approach in managing atopic dermatitis in pediatric patients - Ibarra, Diana M.; Morfin, Ana C.; Coronado, Mariemily A.; Carrillo, Maricarmen; Aguila, Natalia (International Journal of Contemporary Pediatrics, 2023)
Atopic dermatitis is a prominent dermatological condition in children that frequently affects their lifestyle. Conventional treatments frequently prove inadequate, necessitating the use of biological agents like Lebrikizumab to address the condition at its core pathophysiological level. The introduction of biologic drugs has broadened the spectrum of treatment options for patients with moderate to severe atopic dermatitis, especially those who have not achieved satisfactory results with conventional monotherapy or combination therapies, or those with contraindications to systemic immunosuppressive agents. Lebrikizumab appears to be a promising option for the treatment of atopic dermatitis, showing a strong response in clinical trials. It offers the potential for improved long-term efficacy and a reduction in adverse effects. This article provides an overview of Lebrikizumab’s role in addressing the pathogenesis of atopic dermatitis and highlights its current advancements.